2021
DOI: 10.1021/acs.energyfuels.1c03200
|View full text |Cite
|
Sign up to set email alerts
|

Computational Screening and Experimental Synthesis of Doped TiO2 for Propane Dehydrogenation

Abstract: Low-cost, environmentally friendly, and highly efficient catalysts are urgently needed for the direct propane dehydrogenation (PDH) to propylene. Studies have shown that defective TiO2 obtained by in situ reduction shows excellent catalytic PDH performance. Doping metals in the lattice of TiO2 is a plausible method for tuning the vacancy content and electronic property. In this paper, doping with fifth period transition metals was screened using a computational method, followed by experimental synthesis to fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Vanadium-doped TiO 2 was further identified as an effective PDH catalyst (with a C–H activation energy barrier of 0.93 eV) through a computational screening of TiO 2 doped with fourth-period TMs . A similar BEP relationship was obtained for PDH on oxygen-deficient TM–TiO 2– x where Ru–TiO 2– x exhibited the highest PDH activity . Additionally, a linear relationship was identified between the d-band center of the TM dopant on TiO 2 -based catalysts and the adsorption energy of (i) 2-propyl and (ii) 2-propyl&H in the TS, which in turn affect the activation barrier of the first C–H bond activation on propane .…”
Section: Light Alkane (C2–c4) Activation and Dehydrogenation To Olefinsmentioning
confidence: 73%
See 2 more Smart Citations
“…Vanadium-doped TiO 2 was further identified as an effective PDH catalyst (with a C–H activation energy barrier of 0.93 eV) through a computational screening of TiO 2 doped with fourth-period TMs . A similar BEP relationship was obtained for PDH on oxygen-deficient TM–TiO 2– x where Ru–TiO 2– x exhibited the highest PDH activity . Additionally, a linear relationship was identified between the d-band center of the TM dopant on TiO 2 -based catalysts and the adsorption energy of (i) 2-propyl and (ii) 2-propyl&H in the TS, which in turn affect the activation barrier of the first C–H bond activation on propane .…”
Section: Light Alkane (C2–c4) Activation and Dehydrogenation To Olefinsmentioning
confidence: 73%
“…However, under dry conditions, the strong affinity of undercoordinated Ga III for hydride resulted in (i) substantial site blocking with hydride species, especially at high conversions of ethane where a considerable amount of H 2 forms, and (ii) low partial reaction order with respect to ethane (0.40 vs 1.00 in case of pristine γ-Al 2 O 3 ). Song et al performed both experimental and computational studies on PDH using TiO 2 doped with fifth-period TMs and found a linear relationship between PDH TOFs and BE H 2 , where the dissociated hydrogens were both bounded to the dopant TM (Lewis acid site) of the oxygen-deficient TM–TiO 2–x . The more exothermic the BE H 2 , the lower the barrier for the first C–H bond activation and the higher the PDH rate.…”
Section: Light Alkane (C2–c4) Activation and Dehydrogenation To Olefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…12f). 135 Moreover, based on the DFT calculations, Xiao et al pointed out that V-modified TiO 2 also presented higher PDH activity owing to the increased oxygen vacancy content. 138…”
Section: Development Of Pdh Catalystsmentioning
confidence: 99%
“…12f ). 135 Moreover, based on the DFT calculations, Xiao et al pointed out that V-modified TiO 2 also presented higher PDH activity owing to the increased oxygen vacancy content. 138 In general, numerous efforts have been devoted to the development of non-precious metal-based catalysts to substitute the commercial Pt-based and toxic Cr-based catalysts, while it is difficult to meet the requirements of the practical application.…”
Section: Zn-based Catalystsmentioning
confidence: 99%